World Bank Research Digest, Vol. 2(1) - World Bank (Washington, DC, 2014)
In this issue: "Fiscal space" or fiscal policy under constraints? Focus: climate change and agriculture in Africa; how well do institutional theories explain firms' perceptions of property rights? Disability, poverty, and schooling in developing countries; campaign contributions and preferential access to finance; and micro-decomposing the macro determinants of human development; teacher compensation and decentralization in India.